2015
DOI: 10.5899/2015/cacsa-00040
|View full text |Cite
|
Sign up to set email alerts
|

Solving Duffing equation using an improved semi-analytical method

Abstract: Since achieving the precise analytical solution of most nonlinear problems is not possible, numerical methods are meant to be used. In fact a very limited number of nonlinear problems have the exact analytical solution. Let us consider some other methods which are known as semi-analytical methods and applied to solve nonlinear problems. In these methods by using a primary approximation and an iterative process, the approximate solution can be provided, so that the iterations converge to the desired solution. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In Table 1, we compare the AEs achieved using our method with those obtained using the ADM with Legendre and Taylor polynomials (Novin and Dastjerd, 2015) at . Figure 8 plot the AEs of the HPM with shifted Jacobi polynomials, which show that our method (Novin and Dastjerd, 2015) at and for Example 3. is more accurate than HPM with Chebyshev and Taylor polynomials (Behrooz and Ebadi, 2011) shown in Figure 9.…”
Section: Examplementioning
confidence: 99%
See 2 more Smart Citations
“…In Table 1, we compare the AEs achieved using our method with those obtained using the ADM with Legendre and Taylor polynomials (Novin and Dastjerd, 2015) at . Figure 8 plot the AEs of the HPM with shifted Jacobi polynomials, which show that our method (Novin and Dastjerd, 2015) at and for Example 3. is more accurate than HPM with Chebyshev and Taylor polynomials (Behrooz and Ebadi, 2011) shown in Figure 9.…”
Section: Examplementioning
confidence: 99%
“…Figure 8 plot the AEs of the HPM with shifted Jacobi polynomials, which show that our method (Novin and Dastjerd, 2015) at and for Example 3. is more accurate than HPM with Chebyshev and Taylor polynomials (Behrooz and Ebadi, 2011) shown in Figure 9. From Table 1, Figures 8 and 9 listed above, it is shown that the method here is surpassed than ADM with Legendre and Taylor polynomials introduced by Novin and Dastjerd (2015) and the HPM with Chebyshev and Taylor polynomials introduced by Behrooz and Ebadi (2011).…”
Section: Examplementioning
confidence: 99%
See 1 more Smart Citation